(untitled) (Książnica Śląska, 2025)
The article discusses the realisations of three plays by Kazimierz Gołba: Rekruci, My – Pierwsza Kadrowa and Lompa. The first two plays were recorded at the Polish Theater in Katowice in 1935, the latter was an important post-war premiere of the Silesian Theater in June 1945. As noted by Krystian Węgrzynek, Gołbas dramaturgic texts mirror his journalistic activity and constitute the author’s voice in the ongoing debates. In these works the influences of modernist drama are noticeable: historical and naturalistic drama, but also the fascination with monumental drama under the sign of Leon Schiller or Wilam Horzyca